Pengaruh Penanganan Keluhan, Komunikasi Pemasaran dan Kepercayaan terhadap Loyalitas (Literature Review Manajemen Pemasaran) - Hermawati, Agustin (Siber Nusantara Publisher, 2023)
Abstract: Literature review article on the influence of complaint handling, marketing communication and trust on customer loyalty of PT Bank BCA KCU Semarang is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Complaint Handling affects Loyalty; 2) Marketing Communication influences Customer Loyalty; 3) Trust has an effect on Customer Loyalty; Customer. The research was carried out using quantitative methods, as well as a causal relationship research design. The research data is primary data collected through a questionnaire in the form of a google form, as well as secondary data collected by documentation techniques. Sampling was taken using a random sample, while the calculation technique used the Slovin formula so that a sample of 400 was obtained. However, only 150 respondents were willing to fill out the questionnaire. Data analysis technique using multiple regression analysis. Abstrak: Artikel Literatur Review Pengaruh Penanganan Keluhan, Komunikasi Pemasaran dan Kepercayaan terhadap Loyalitas nasabah PT Bank BCA KCU Semarang dalah artikel ilmiah yang bertujuan membangun hipotesis riset pengaruh antar variabel yang akan digunakan pada riset selanjutnya, dalam ruang lingkup ilmu Manajemen Pemasaran. Metode penulisan artikel Literature Review ini adalah dengan metode library risearch, yang bersumber dari media online seperti Google Scholar, Mendeley dan media online akademik lainnya. Hasil artikel Literature Review ini adalah: 1) Penanganan Keluhan berpengaruh terhadap Loyalitas; 2) Komunikasi Pemasaran berpengaruh terhadap Loyalitas Nasabah; 3) Kepercayaan berpengaruh terhadap Loyalitas Nasabah; Nasabah. Penelitian dilaksanakan dengan metode kuantitatif, serta desain penelitian hubungan kausal. Data penelitian adalah data primer yang dikumpulkan melalui kuesioner berbentuk google form, serta data sekunder yang dikumpulkan dengan teknik dokumentasi. Pengambilan sampel dengan random sampel, sedangkan teknik penghitungannya menggunakan rumus Slovin sehingga diperoleh sampel sebanyak 400. Namun hanya 150 responden yang bersedia mengisi kuesioner. Teknik analisis data menggunakan analisis regresi berganda.